Safety and effectiveness of monovalent COVID-19 mRNA vaccination and risk factors for hospitalisation caused by the omicron variant in 0.8 million adolescents: A nationwide cohort study in Sweden - Nordström, Peter; Ballin, Marcel; Nordström, Anna (PLoS medicine, 2023)
Real-world evidence on the safety and effectiveness of Coronavirus Disease 2019 (COVID-19) vaccination against severe disease caused by the omicron variant among adolescents is sparse. In addition, evidence on risk factors for severe COVID-19 disease, and whether vaccination is similarly effective in such risk groups, is unclear. The aim of the present study was therefore to examine the safety and effectiveness of monovalent COVID-19 mRNA vaccination against COVID-19 hospitalisation, and risk factors for COVID-19 hospitalisation in adolescents. A cohort study was conducted using Swedish nationwide registers. The safety analysis included all individuals in Sweden born between 2003 and 2009 (aged 11.3 to 19.2 years) given at least 1 dose of monovalent mRNA vaccine (N = 645,355), and never vaccinated controls (N = 186,918). The outcomes included all-cause hospitalisation and 30 selected diagnoses until 5 June 2022. The vaccine effectiveness (VE) against COVID-19 hospitalisation, and risk factors for hospitalisation, were evaluated in adolescents given 2 doses of monovalent mRNA vaccine (N = 501,945), as compared to never vaccinated controls (N = 157,979), for up to 5 months follow-up during an omicron predominant period (1 January 2022 to 5 June 2022). Analyses were adjusted for age, sex, baseline date, and whether the individual was born in Sweden. The safety analysis showed that vaccination was associated with 16% lower (95% confidence interval (CI) [12, 19], p < 0.001) risk of all-cause hospitalisation, and with marginal differences between the groups regarding the 30 selected diagnoses. In the VE analysis, there were 21 cases (0.004%) of COVID-19 hospitalisation among 2-dose recipients and 26 cases (0.016%) among controls, resulting in a VE of 76% (95% CI [57, 87], p < 0.001). Predominant risk factors for COVID-19 hospitalisation included previous infections (bacterial infection, tonsillitis, and pneumonia) (odds ratio [OR]: 14.3, 95% CI [7.7, 26.6], p < 0.001), and cerebral palsy/development disorders (OR: 12.7, 95% CI [6.8, 23.8], p < 0.001), with similar estimates of VE in these subgroups as in the total cohort. The number needed to vaccinate with 2 doses to prevent 1 case of COVID-19 hospitalisation was 8,147 in the total cohort and 1,007 in those with previous infections or developmental disorders. None of the individuals hospitalised due to COVID-19 died within 30 days. Limitations of this study include the observational design and the possibility of unmeasured confounding. In this nationwide study of Swedish adolescents, monovalent COVID-19 mRNA vaccination was not associated with an increased risk of any serious adverse events resulting in hospitalisation. Vaccination with 2 doses was associated with a lower risk of COVID-19 hospitalisation during an omicron predominant period, also among those with certain predisposing conditions who should be prioritised for vaccination. However, COVID-19 hospitalisation in the general population of adolescents was extremely rare, and additional doses in this population may not be warranted at this stage.